Rehabilitation of pumps: case study of universal pump set (2003)
Laboratory equipment is meant to impart some modules of knowledge unto students of engineering and applied sciences. In other words they are to bridge the gap between theory in the classroom and practical on the field. When there is no sufficient fund to keep this equipment in good condition other avenues must be looked into to avert the dangers of training Engineers and Technicians without the necessary exposure to Laboratory practicals. Equipment worth millions of Naira are lying waste in many institutions of higher learning because nobody cared to take the bull by the horns. The purpose of this project is to rehabilitate laboratory equipment that had been abandoned for many years due to malfunctioning of one or two components. The approach adopted here was to find out the root cause of the problem and proffered a solution. This was done in the case of Universal Water Pump Set located in the fluid laboratory of Mechanical Engineering Department, University of Ibadan, Ibadan. The rig was tested after the repair and maintenance exercises were carried out. The results of performance characteristics carried out on the equipment confirmed that it has been brought back to life. Two laboratory exercises were prepared for each pump to be used by the students as from the next session. The total cost of rehabilitation excluding labour was N1700.00.